A modeling study by response surface methodology on the culture parameters optimization of citric acid bioproduction from sweet potato peel - Oyeniran, O.O.; Taiwo, A.E.; Betiku, Eriola (Ife Journal of Technology, 2013)
The study investigated the use of sweet potato peel hydrolysate (SPPH) as a potential substrate for citric acid (CA) production. Effect of methanol on the synthesis of CA was initially investigated. The fermentation process involved was optimized by the application of response surface methodology (RSM) to determine the effect of SPPH concentration, methanol concentration, and time, and their reciprocal interactions on CA amount produced. The highest CA concentration was observed on the 4th day of fermentation and the medium induced with methanol produced higher amount of CA (16 g/l) than medium without methanol supplementation (11.37 g/l). The results obtained for the optimization studies showed that a statistically significant (p<0.05) quadratic model best described the fermentation process. The highest CA predicted using the quadratic model obtained was 15.97 g/l at the optimal condition of SPPH concentration of 150 g/l, time of 3.61 days, and methanol concentration of 3 volume %. Using these optimal condition values in setting up three independent replicates, an average experimental value of 15.98 g/l was obtained, which was well within the range predicted by the model. This work demonstrated that SPPH could serve as an inexpensive and novel feedstock for CA bioproduction.